Phylogenetic Analysis and Time Divergence of Genus Musa spp. Using S16 Protein Genes (Rps16) Intron Chloroplast - Noor, Farah Nahdia; Sholichah, Lailatus (Future Science, 2019)
Family Musaceae is divided into three genera, Musa, Musella, and Ensete. The genus Musa became the genus with the most species cultivated in the Southeast Asian region. While the genus Musella and Ensete are monospecific genera that can only be found in certain regions. Distribution of banana nomenclature until now is still a debate. The taxonomic system of bananas is still based on conventional methods, namely by marking the genome. But unfortunately the nomenclature system is not suitable to be applied in the Southeast Asian region. The systematic history of the genus Musa apparently still has many problems such as biogeography, the comparison of phylogenetic trees and their evolution. Therefore be approached through an m arka molecular phylogenetic alisis menggunakan g en protein S16 (Rps16) chloroplast introns with Bayesian inference method and divergence time estimates using the log-normal clock relaxed. The results show that the tree topology produced monophyletic lineage, in terms of the separation of the genus Musa from the Musella lasiocarpa and Ensete ventricosum Outgroups